Evaluation of the Effects of Ankle Foot Orthosis on the Performance of the Subjects with Knee Joint Osteoarthritis. - Kaviani Broojeni, Mahsa; Karimi, Mohammad Taghi (Physical & Occupational Therapy in Geriatrics, 2024)
The aim of this review was to evaluate the efficiency of using ankle foot orthosis (AFO) on the loads applied on the knee joint in the subjects with knee osteoarthritis (OA) based on available literature. A search was done in some data bases including Medline, PubMed, Cochrane central register of controlled trial (CCTR), Embase, and ISI web of knowledge. The key words selected by national library of medicine were selected in this study. Those included Ankle foot orthosis (AFO) in combination with knee osteoarthritis (OA). Based on the aforementioned key words, 25 papers were selected. Based on abstracts and titles, 9 papers were finalized. AFO reduces knee adduction moment, which is more than lateral wedge. Moreover, AFO is more comfortable than other interventions. Although use of AFO reduces knee adduction moment, its effect on pain and functional performance is still controversial.